Anatomy of the Mediastinum Testis of Goat (Capra hircus) - A Temporal Study - Pathak, Archana; Katiyar, R. S.; Sharma, D. N. (Indian Journal of Veterinary Anatomy, 2015)
Both testes from apparently and sexually healthy 30 male Gaddi goats( prepubertal, pubertal and post pubertal) were collected with 10 animals in each. A mediastinum testis was an axial connective tissue strand extending from caput to ventral Â¾ of the testicles. It was connected to the tunica albuginia by means of peripherally radiating septae. Grossly the mediastinum was loose and gelatinous in new born kids but dense and white fibrous type in older animals. Histologically, it comprised of connective tissue rich in reticulin in pre pubertal, elastin, reticulin and collagen in pubertal and mostly collagen in post pubertal animals. Blood vessels, rete testes and tubuli recti formed their integral part. Tubuli recti were luminated straight tubule lined with simple cuboidal epithelium whereas, rete testes which were smaller in group-I became larger and irregular in Group-II and variable sac like in Group-III, lined with low columnar to cuboidal to squamous epithelium. Histochemically the tubuli recti and rete testes were very active as evidenced by the presence of PAS, Alcian blue, alkaline phosphatase, acid phosphatase reactions. The inetensity of these reactions was affected a little only as per age, but the lipid and protein reactions were significantly increased in Group-II and Group-III.